Long trumpets of northern Nigeria - in history and today - Gourlay, Ken A. (International Library of African Music, 1982)
A visitor arriving at Kano International Airport in northern Nigeria on the same flight as a local V.I.P. may find himself greeted by a blast on an instrument which, at first sight, suggests an elongated European hunting horn or that used by postillions of eighteenth century stage-coaches. It may remind him of the long, straight trumpet in Giotto’s Crowning of the Virgin (ca. 1317) or of the instruments on the medallion from Guerrero Lovillo’s Cantigas de Santa Maria on the sleeve of H.M.V.’s “Early Medieval Music”. Of the quotations at the head of this article the second would seem an appropriate description, but in fact refers to a Chinese trumpet of the later middle ages. It is the first which records the earliest sighting of a Nigerian long trumpet by a British explorer, the ill-fated Oudney, in a letter home on 28th March 1823. The starting point for any enquiry is to discover the link between present day Nigerian and medieval Chinese or European trumpets and to investigate what happened to those made of wood.
Keywords: Musical instruments; Trumpet; African Music; Nigeria; Long Trumpet (Instrument)